2014
DOI: 10.1371/journal.pone.0087358
|View full text |Cite
|
Sign up to set email alerts
|

Is Housing Quality Associated with Malaria Incidence among Young Children and Mosquito Vector Numbers? Evidence from Korogwe, Tanzania

Abstract: BackgroundSeveral studies conducted in Northeast Tanzania have documented declines in malaria transmission even before interventions were scaled up. One explanation for these reductions may be the changes in socio-environmental conditions associated with economic development, and in particular improvements in housing construction.ObjectiveThis analysis seeks to identify (1) risk factors for malaria incidence among young children and (2) household and environmental factors associated with mosquito vector number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 33 publications
4
51
1
Order By: Relevance
“…There is increasing evidence to support a crucial role for housing improvement in malaria control [31–33, 60, 61]. It can be envisaged that ITWL could act as an effective and insecticidal method of house, and in particular, eave screening, if affixed to the base of the roof or ceiling and proven to have long-term durability.…”
Section: Future Prospects Of Itwl For Malaria Control: Control Intervmentioning
confidence: 99%
“…There is increasing evidence to support a crucial role for housing improvement in malaria control [31–33, 60, 61]. It can be envisaged that ITWL could act as an effective and insecticidal method of house, and in particular, eave screening, if affixed to the base of the roof or ceiling and proven to have long-term durability.…”
Section: Future Prospects Of Itwl For Malaria Control: Control Intervmentioning
confidence: 99%
“…In the recent past, house modification through window screen and blocking of eaves has been practiced in the prevention of malaria vectors in Tanzania [30,31], Kenya [32] Ethiopia [33] and Uganda [34]. More innovative vector control strategies including control of resistant vector populations in the sub-region are use of entomopathogenic fungi [35,36], larval source management [7] and vector trapping [37][38][39].…”
Section: Malaria Prevention and Control Strategies In East Africamentioning
confidence: 99%
“…13 In a larger study of intermittent preventive treatment of malaria conducted in Tanzania, high-quality housing based on an index of dwelling characteristics was associated with a lower incidence of malaria and vector density. 21 Quality housing is thought to provide protection from malaria by blocking entry and reducing the density of the mosquito vector. Poor-quality material used for walls, such as mud, may provide more entry points through cracks in their surface.…”
mentioning
confidence: 99%
“…Other studies reporting similar associations between poor house construction and an increased incidence of malaria have successfully included this absent information to give a clearer picture. 21 Another limitation is self-reported ITN use. Over 98% study participants reported sleeping under an ITN the previous night at the time of routine assessments, however, actual compliance with ITNs was not confirmed through visual inspection at the home.…”
mentioning
confidence: 99%